把4(x-y+1)+y(y-2x)因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 07:16:08
把4(x-y+1)+y(y-2x)因式分解
把4(x-y+1)+y(y-2x)因式分解
把4(x-y+1)+y(y-2x)因式分解
4(x-y+1)+y(y-2x)
=4x-4y+4+y^2-2xy
=(y^2-4y+4)-2x(2-y)
=(y-2)^2+2x(y-2)
=(y-2)(2x+y-2)
4(x-y+1)+y(y-2x)
=4x-4y+4+y^2-2xy
=y^2-4y+4-2xy+4x
=(y-2)^2-2x(y-2)
=(y-2)(y-2-2x)
4(x-y+1)+y(y-2x)
=4x-4y+4+y^2-2xy
=(y^2-4y+4)-2x(2-y)
=(y-2)^2+2x(y-2)
=(y-2)(2x+y-2)
4(x-y+1)+y(y-2x)
=4x-4y+4+y^2-2xy
=(y^2-4y+4)-2x(2-y)
=(y-2)^2+2x(y-2)
=(y-2)(2x+y-2)
4(X-Y+1)+Y(Y-2Y)
=4X-4Y+4+Y*Y-2XY
=Y*Y-4Y+4+4X-2XY
=(Y-2)*(Y-2)+2X(2-Y)
=(Y-2)*(Y-2)-2X(Y-2)
=(Y-2)(Y-2-2X)
4(x-y+1)+y(y-2x)
=4x-4y+4+y2-2xy
=(2-y)2+2x(2-y)
=(2-y)(2+2x)
(x-y+1)+y(y-2x)
=4x-4y+4+y2-2xy
=(2-y)2+2x(2-y)
=(2-y)(2+2x)
二、五楼的对
4(x-y+1)+y(y-2x)
= 4x-4y+4+y^2-2xy
= (y^2-4y+4)-2x(2-y)
= (y-2)^2+2x(y-2)
= (y-2)(2x+y-2)
2,5是对的。